Beveling the Colorado Plateau: Early Mesozoic Rift‐Related Flexure Explains Erosion and Anomalous Deposition in the Southern Cordilleran Foreland Basin. Issue 6 (7th June 2021) - Chapman, James B.; DeCelles, Peter G.
Abstract: Deposition of the Late Jurassic Morrison Formation in a back‐bulge depozone and formation of the overlying sub‐Cretaceous unconformity above a forebulge mark the birth of the foreland basin system in the central U.S. Cordillera. In the southern U.S. Cordillera, the Morrison Formation is either anomalously thick or absent and the sub‐Cretaceous unconformity cuts out progressively older stratigraphy toward the south on the Colorado Plateau. Based on results of 2D and 3D flexural modeling, we suggest that flexural uplift of the northern rift flank of the Bisbee segment of the Borderland Rift Belt can explain these observations. Structural restoration of the sub‐Cretaceous unconformity indicates a minimum of 1.5 km of uplift and flexural models with an effective elastic thickness of 55 ± 5 km can reproduce the geometry of the unconformity and rift flank. This implies that effective elastic thickness has decreased between the Jurassic and the present, consistent with hypotheses for uplift and modification of the Colorado Plateau lithosphere during the Late Mesozoic to Cenozoic. Modeling results also predict the presence of a rift‐related flexural trough in the Four Corners region of the Colorado Plateau, which may explain above‐average thickness of the Morrison Formation. Constructive interference between a flexural back‐bulge depozone and a flexural rift‐flank trough may help explain anomalously high Late Jurassic subsidence. Plain Language Summary: Continental rifting in southern Arizona during the Jurassic caused the margins of the rift system to be flexed upward and eroded. The erosion resulted in a regionally extensive, low‐angle unconformity beneath Cretaceous sedimentary rocks in the southern Colorado Plateau. As the rift margin was flexed upward it caused nearby parts of the rigid crust to flex downward in response, specifically in the Four Corners region of the Colorado Plateau (approximately where the state boundaries of Arizona, New Mexico, Colorado, and Utah meet). The downward flexure in the Four Corners area created a basin where sediments of the Morrison Formation accumulated and are thicker than anywhere else in the western U.S. Key Points: The sub‐Cretaceous unconformity in the southern Colorado Plateau can be explained by flexural uplift of the northern flank of the Bisbee Rift system Flexure of the rift flank also resulted in an outer low or depositional trough in the Four Corners region of the plateau The anomalous thickness of the Morrison Formation in the Four Corners region is related to constructive flexural interference between a back‐bulge depozone related to the Sevier thrust belt and a flexural trough related to rift flank flexure